Deliberate Negligence: Bolsonaro and Brazil’s Failure in Response to COVID-19 Pandemic - Yohanes William Santoso (Global Strategis, 2020)
Brasil merupakan negara dengan kasus positif COVID-19 tertinggi kedua di dunia, setelah Amerika Serikat. Kasus penularan dan kematian yang tinggi membuat Brasil dapat dikatakan gagal dalam mencegah penyebaran COVID-19. Terdapat beberapa faktor yang berpengaruh dalam kegagalan upaya Brasil merespon pandemi ini. Salah satunya adalah karena adanya informasi dan instruksi yang berbeda antara Presiden Bolsonaro dengan gubernur-gubernurnya. Tulisan ini bertujuan untuk mengkaji respon Brasil dalam mengatasi pandemi COVID-19 dari rentang waktu sejak kasus pertama pada bulan Februari hingga bulan Juli 2020, serta menjelaskan alasan kegagalan tersebut. Argumen utama penulis adalah kegagalan Brasil disebabkan oleh adanya gejolak dalam politik domestik Brasil, dan kondisi sosial ekonomi di Brasil. Gejolak politik domestik tersebut dibagi menjadi dua yaitu gejolak di tingkat nasional: antara Presiden Bolsonaro dan menteri kesehatannya; dan gejolak di tingkat lokal: antara Presiden Bolsonaro dengan para gubernur negara bagian. Dari segi ekonomi, kondisi Brasil yang masih berusaha memulihkan perekonomian membuat pemerintahan Bolsonaro seolah sengaja melalaikan tanggung jawab untuk mengatasi penyebaran COVID-19. Sementara dari segi sosial, ketimpangan yang ada di Brasil membuat masyarakat yang tinggal di daerah-daerah miskin menjadi paling beresiko tertular karena tidak adanya infrastruktur sanitasi yang memadai. Kata-kata kunci: COVID-19, Brasil, Bolsonaro, kelalaian Brazil is a country with the second highest positive cases of COVID-19 in the world, after the United States. The high number of infected and death cases makes Brazil fail to prevent the spread of COVID-19. There are several factors contributed to Brazil's failure to respond the pandemic. One of the reasons is because of the information and differences between President Bolsonaro and his governors. This paper aims to examine Brazil's response in overcoming the COVID-19 pandemic from the timeframe from the first case in February to July 2020, and to explain the reasons for this failure. The author’s main argument is that Brazil's failure was caused by the turmoil in domestic politics and the socio-economic conditions in Brazil. Domestic political turmoil is divided into two, namely turmoil at the national level: between President Bolsonaro and his ministers of health; and turmoil at the local level: between President Bolsonaro and state governors. From the economy point of view, Brazil's condition, which is still in recovery, has made the Bolsonaro administration seem to have deliberately neglected its responsibility to contain the spread of COVID-19. Meanwhile, from a social perspective, the existing inequality in Brazil put people living in poorest regions at the highest risk of infection due to the absence of adequate sanitation infrastructure. Keywords: COVID-19, Brazil, Bolsonaro, negligence